Comparative analysis of stomatological indicators in children and teenagers with arterial hypertension - L. R. Kolesnikova; L. V. Natyaganova; T. K. Shkavro (Acta Biomedica Scientifica)
The frequency of dental diseases among children and teenagers is increasing. The development of diseases is influenced by both local and general factors. The common factors include somatic diseases, in this case that is arterial hypertension. Having examined the children and teenagers with arterial hypertension, we identified the degree of caries and diseases of parodont, evaluated oral health status. We have not revealed changes in the latter. Thefirst expressed manifestations of periodontal tissues diseases were identified in the groups with arterial hypertension. Activity of caries process indicated higher rates in the groups with arterial hypertension. With age, the frequency and intensity of these diseases increase.